Do Cytomegalovirus Antibody Levels Associate with Age-Related Syndromes in HIV Patients Stable on Antiretroviral Therapy? - Brunt, S.; Cysique, L.; Lee, Silvia; Burrows, S.; Brew, B.; Price, Patricia (Mary Ann Liebert, Inc., 2016)
HIV+ persons stable on antiretroviral therapy (ART) face early onset of age-related diseases. This may arise from a high burden of cytomegalovirus (CMV). To address the role of CMV, we investigated univariate and multivariate associations between markers of systemic and endothelial inflammation, vascular damage, insulin resistance (IR), neurocognitive decline, and antibodies reactive with CMV. In this study, HIV+ participants (n = 91) aged >45 years with <50 copies HIV RNA/ml plasma after >2 years on ART were assessed for cardiovascular risk (the D:A:D algorithm), type II diabetes (the HOMA-IR index), and neurocognitive performance. Blood samples were assayed for lipids, T cells, insulin, glucose, C-reactive protein, CX3CL1, sTNF-R1, total immunoglobulin G (IgG), and antibodies reactive with CMV lysate, glycoprotein B, or immediate-early-1. Levels of antibodies detected with the three antigens were tightly correlated.Levels of CMV lysate antibody were higher in patients than in age-matched healthy controls and reflected their nadir CD4 T-cell count (p = .001), total IgG (p = .02), and age (p = .08). Levels of CMV lysate antibody correlated with D:A:D score (p = .04), neurocognitive performance (p = .045), and fasting insulin (p = .02). In multivariable analyses, some associations reflected the effect of age, but CMV lysate antibody and CD8 T-cell counts were significant predictors of the HOMA-IR index (R2 = 0.09, p = .01) independent of age. We conclude that associations between levels of CMV antibodies, cardiovascular risk, and neurocognitive health in HIV+ patients stable on ART are moderated by age-associated increases in response to CMV, while CMV antibodies may be independently linked with IR.